IMPLEMENTASI PROJECT BASED LEARNING DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN KONSEP DIRI SISWA - AMINULLAH, AMINULLAH (GANEC SWARA, 2018)
This study aims to describe how to improve student self-concept through the implementation of project based learning with scientific approach. The research design used is Classroom Action Research Kemmis and Taggart model by dividing the action research procedure in four stages of activity on one cycle (cycle), namely: planning, action, observation and reflection. Subjects in this study were students of class VIII which amounted to 33 students. The research data was collected using questionnaire instrument, observation sheet and test and data analysis using quantitative descriptive statistical analysis with the success criteria of the action seen from the average ability of self-concept of students ≥ 74.45 and percentage of learning based learning project with scientific approach ≥ 85%. The research or action ended in cycle II in the second meeting with the results of the study showed: students' self-concept ability with an initial average of 70.58 to 75.15 in the high category, while individually from the initial condition of students who categorized as very high 3.03 % to 21, 21%, medium category from 36, 36% to 18, 18%. Learning using project based learning with scientific approach at the end of the second cycle reached 94% and students who passed KKM 93, 94% with an average student 84, 70 from the target average student ≥ 75 or complete ≥ 75%.